2017
DOI: 10.22581/muet1982.1701.11
|View full text |Cite
|
Sign up to set email alerts
|

Volt/VAr Optimization of Distribution System with Integrated Distributed Generation

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…More shinyo synchronization in the iteration process, the work node first qualifying examination parameters obtained from the parameter server model, where each work node access is the same parameters, and then work nodes for training, after the completion of the training to the server sends parameters variation or gradient, parameters after the server to get all work node sends information to carry on the average, The global model on the parameter server is updated by gradient descent [15]. The synchronous update process is shown in Figure 1, and the formula is as follows:…”
Section: Figure1synchronously Update the Architecture Diagrammentioning
confidence: 99%
“…More shinyo synchronization in the iteration process, the work node first qualifying examination parameters obtained from the parameter server model, where each work node access is the same parameters, and then work nodes for training, after the completion of the training to the server sends parameters variation or gradient, parameters after the server to get all work node sends information to carry on the average, The global model on the parameter server is updated by gradient descent [15]. The synchronous update process is shown in Figure 1, and the formula is as follows:…”
Section: Figure1synchronously Update the Architecture Diagrammentioning
confidence: 99%
“…Celli et al [18] suggested Multi-Objective (MO) GA considering the ɛ-constraint method to find the feasible solutions of optimum DG capacity and site. Moreover, lot of research work is existed in the literature to find appropriate site and size of DG, that includes analytical approach [19], Genetic Algorithm (GA) [20], Bacterial Foraging Optimization (BFO) in [21], Artificial Neural Network (ANN) [22], Multi-Objective Particle Swarm Optimization (MOPSO) in [23]. Recently few numbers of studies have been accomplished to novelty simultaneously DG allocation and OFR, in which Adaptive CSA (ACSA) [24], Harmony Search Algorithm (HSA) [5], and Fireworks Algorithm (FWA) [25] are up-to-date few of the methods.…”
Section: Introductionmentioning
confidence: 99%